Nurse parasite clinics and the benefits of routine testing. (2nd July 2021) - Wright, Ian; Richmond, Philippa
Abstract : Cats and dogs are infected with a wide range of parasites, many of which are capable of causing or contributing to disease. Veterinary nurses play a vital role in helping to formulate parasite control plans for pets. Routine diagnostic testing alongside risk-based appropriate preventative treatment is important for efficacy of treatment to be monitored, screening for sub-clinical parasitic infections and drug resistance and to demonstrate that current parasite control recommendations are adequate. A wide range of diagnostic tools are available to veterinary practices and this article considers some of the diagnostic techniques available for routine parasite diagnosis and how they might be used in parasite prevention plans for cats and dogs.